Pelatihan Website Manajemen Barang dan Keuangan Pada Usaha Meka Tailor di Desa Saba - Luh Putu Safitri Pratiwi; I Made Pasek Pradnyana Wijaya; A. A Ayu Meitridwiastiti; Wayan Astu Werdistira (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
Mrs. Nyoman Mekawati, a skilled seamstress who operates in the Saba Village area, Gianyar Regency. He has been in this business for approximately three years. During this period there were several obstacles, one of which was regarding the management of fabric stocks. The fabric stock owned is placed in boxes or sacks. When they receive an order, partners sometimes buy more fabric but it turns out there is still fabric stock that can be used. Sometimes partners forget to buy the fabric at the same price and charge the same price for fabrics of different prices. The aim of this service activity is to create a website-based goods and financial management information system owned by Meka Tailor. Furthermore, website training on goods and financial management was held for tailor businesses. From the service activities carried out, a website-based goods and financial management information system has been successfully built and can help partners in managing stock of goods and also monitoring their business finances. Partners also feel helped by the system that was built along with training in using the system.